The Industrial design: reference + specification book. : Everyting industrial designers need to know every day - Cuffaro, Daniel F., ....-; Paige, Douglas, ....-; Blackman, Carla J., ....- (Beverly (Mass.) : Rockport Publishers, 2013)
O make designs that work and endure (and are also legal), designers need to know—or be able to find—an endless number of details. Whether it's what kind of glue needs to be used on a certain surface, metric equivalents, thread sizes, or how to apply for a patent, these details are essential and must be readily available so designers can create successful products efficiently. The Industrial Design Reference & Specification Book provides designers with a comprehensive handbook they can turn to over and over again. These pages are filled with information that is essential to successful product design, including information on measurement conversions, trademark and copyright standards, patents and product-related intellectual property rights/standards, setting up files for prototyping and production runs, and manufacturing and packaging options to optimize the design. It is an essential resource for any industrial or product designer.
Keywords: Industrial design